Choroidal measurements in patients affected by PXE-related retinopathy - Mucciolo, Dario Pasquale; Murro, Vittoria; Giorgio, Dario; Boraldi, Federica; Pavese, Laura; Quaglino, Daniela; Sodi, Andrea; Branchetti, Marco; Pollazzi, Liliana; Virgili, Gianni; Giansanti, Fabrizio (Frontiers in Ophthalmology, 2025)
PurposeTo investigate the choroid in patients affected by pseudoxanthoma elasticum (PXE)-related retinopathy using the choroidal vascularity index (CVI).MethodsPXE patients and controls were recruited at the Eye Clinic in Florence. High-resolution imaging optical coherence tomography (OCT) scans (12 × 9 mm) of 32 PXE patients and 20 age-matched controls were examined. Images were binarized using the ImageJ software, and subfoveal choroidal thickness (SFCT), luminal area (LA), stromal area (SA), total choroidal area (TCA), and CVI were measured.ResultsSixty-four eyes of 32 PXE patients (mean age 45.65 ± 16.12; range 14–69) and 40 eyes of 20 controls (mean age 47.3 ± 13.7; range 18–71) were included in the study. SFCT was significantly lower in PXE patients compared to controls. The LA, SA, and TCA of the PXE patients were significantly reduced in comparison with those obtained for controls (p = 0.012, p < 0.001, and p = 0.001, respectively). On the contrary, the CVI did not significantly differ between patients and controls (p = 0.744). In young subjects, differences regarding SFCT, LA, SA, TCA, and CVI were not detected between PXE patients and healthy controls (p = 0.170, p = 0.990, p = 0.264, p = 0.351, and p = 0.487, respectively).ConclusionIn PXE-related retinopathy, choroidal impairment appears progressive with age, and there is a simultaneous, proportional impairment of both the stromal and vascular components of the choroid.